2015
DOI: 10.1128/iai.01074-15
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Infections Caused by Methicillin-Resistant Staphylococcus aureus Are Linked to Clonal Complex-Specific Alterations in Binding and Invasion Domains of Fibronectin-Binding Protein A as Well as the Occurrence of fnbB

Abstract: e Endovascular infections caused by Staphylococcus aureus involve interactions with fibronectin present as extracellular matrix or surface ligand on host cells. We examined the expression, structure, and binding activity of the two major S. aureus fibronectinbinding proteins (FnBPA, FnBPB) in 10 distinct, methicillin-resistant clinical isolates from patients with either persistent or resolving bacteremia. The persistent bacteremia isolates (n ‫؍‬ 5) formed significantly stronger bonds with immobilized fibronec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Consistent with this, increased FN binding of cfr-positive MRSA correlated with worse outcomes of linezolid-based mono-and combination therapies in the murine bacteremia model. This observation is also in line with previous reports that the development of a hyper-adhesive FN binding phenotype contributed to persistent MRSA bacteremia and infective endocarditis (Xiong et al, 2009(Xiong et al, , 2015. In addition, we found that cfr-positive MRSA isolates adhered better than cfr-negative isolates to human endothelial cells, and this may facilitate MRSA colonization and provide an advantage in the pathogenesis of invasive MRSA infections.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with this, increased FN binding of cfr-positive MRSA correlated with worse outcomes of linezolid-based mono-and combination therapies in the murine bacteremia model. This observation is also in line with previous reports that the development of a hyper-adhesive FN binding phenotype contributed to persistent MRSA bacteremia and infective endocarditis (Xiong et al, 2009(Xiong et al, , 2015. In addition, we found that cfr-positive MRSA isolates adhered better than cfr-negative isolates to human endothelial cells, and this may facilitate MRSA colonization and provide an advantage in the pathogenesis of invasive MRSA infections.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, we discovered nonsynonymous SNPs in high-affinity repeats of FnBPA, such as FnBR-9, that were associated with several distinct S. aureus syndromes in humans: H782Q/ K786N with cardiac device infections (12,13) and H782Q/ K786I with persistent bacteremia and infective endocarditis (14). This correlation has been externally corroborated (15).…”
Section: Energy Landscape For Dissociation Of Fn⅐fnbr-9 Bondmentioning
confidence: 84%
“…H782Q/K786I exhibited higher affinity for immobilized Fn at fast loading rates versus the alanine peptide (⌬⌬G 0.81 kcal/ mol; Table 2), but binding was weaker than for the wild-type and Gln/Asn peptides. This is not entirely unexpected because the Gln/Ile polymorphisms (unlike the Gln/Asn polymorphisms) are associated with persistent bacteremia in patients who do not necessarily have a cardiovascular implant (14). The Gln/Ile isolates are also associated with a host invasion motif (GIDFVED) in FnBR-11 and an extra repeat of FnBR-9 giving these strains a total of 12 rather than 11 FnBRs (14,15).…”
Section: Energy Landscape For Dissociation Of Fn⅐fnbr-9 Bondmentioning
confidence: 94%
See 2 more Smart Citations